PENGARUH PROMOSI DAN KEPERCAYAAN TERHADAP MOTIVASI MUZAKKI PADA BAZNAS PROVINSI KALIMANTAN TIMUR - Purwanti, Purwanti (LPPM University 17 Agustus 1945 Samarinda, 2020)
The purpose of the research was : 1) to the determine the effect of promotion on muzakki motivation, and 2) to find out the effect of trust in muzakki motivation on BAZNAS in East Kalimantan. The research used a quantitative approach. The sample in the research was taken using purposive sampling technique. To collect data, researcher use research instrumens, questionnaires. The population in the research was muzakki which distributed zakat to BAZNAS of East Kalimantan province while the sample was muzakki which distributed zakat to the BAZNAS of East Kalimantan province through UPZ, Each UPZ was taken 3 muzakki to fill the quetionnary. Based on the results of the data validity test, the statement on the research questionnaire was declared valid therefore it could be used fot the next test, that was reliability testing. The results of the multicollinearity test showed no multicollinearity. Heterocedasticity test results showed no problems with heterocedasticity. The autocorrelation test results showed no autocorrelation. The test results for the significance of the test were 0,292 or 29,2%. The results of multiple linier regression analysis formed the equation Y = 28,461-0,36X1 + 0,246X2. From the equation obtained a constant 28,461. Thus the promotion variable ad a significant negative effect while the trust variable had appositive and significant effect. The results of the F test state that promotion and trust variables simultaneously (together) influenced motivation of muzakki whilw partially the trust had a positive and significant effect on the motivation of muzakki in the BAZNAS of East Kalimantan Province.Keywords : promotion, trust and motivation